Analisis Miskonsepsi Pembelajaran Kepemimpinan Strategis dengan Certainty Response Index (CRI) - Tjandra Ariwibowo (JURNAL PENDIDIKAN DAN PELATIHAN PERTAHANAN, 2026)
Leadership strategy science has become a learning model that can be applied to an organization's human resources in the face of today's highly dynamic developments in various fields. Its application in education and training is used to formulate policy directions in this era of technological disruption, to develop individuals with leadership skills/intuition as the next generation of organizational leaders. This study uses the Certainty Response Index method to assess the correct understanding of leadership concepts, misunderstandings, or misconceptions. The results show that some participants have misconceptions. The element of long-term value creation has the most misconceptions, followed by the other three elements. The CRI diagnostic approach to strategic leadership material is new, whereas the previous CRI diagnostic approach was used in science and law.  Misunderstandings in several elements of strategic leadership material indicate that the quality of the learning process needs to be improved. The learning process that needs to be improved includes learning strategies, learning methods, and formative evaluation, so that participants' understanding can be improved. Optimizing the learning process is very important to produce higher quality education and training outcomes.